Floristic composition and ecological distribution of vascular epiphytes in the National Forest of Passo Fundo, Rio Grande do Sul - Buzatto, Cristiano Roberto (2008)
Vascular epiphytes are a common feature of tropical and subtropical humid forests around the world. A floristic survey was conducted in a mixed araucaria forest at the Passo Fundo National Forest (29º16’ S and 52º18’ W), near Mato Castelhano, Rio Grande do Sul. The floristic survey resulted in 44 species, from 28 genera and 12 families. Orchidaceae (13),Polypodiaceae (8) and Bromeliaceae (6) were the most species-rich families. Richness varied from 9 to 30 species, respectively on the trunks of tree-ferns and on the crowns of canopy trees. The most frequent species were Peperomia catharinae (Piperaceae) and three species of ferns, Campyloneurum nitidum, Microgramma squamulosa, and Pleopeltis angusta (Polypodiaceae). Multivariate analysis distinguished two groups, one including trees with rough bark, and another including specialized habitats, like branches of araucaria, Myrtaceae with smooth bark, and caudices of tree-ferns. Epiphytic richness in the studied area is lower than in other stands of mixed araucaria forests of South Brazil, probably as a consequence of the relatively southern and continental try conditions, which reduces the influence of the highly-diversified atlantic rain-forests.